Implementasi Sistem Pendukung Keputusan Berbasis Metode Simple Additive Weighting untuk Rekrutmen Sumber Daya Manusia - Oslan Juliana Simbolon; Sitompul, Pandapotan; Tarigan, Miska Irani Br; Sitanggang, Lestari; Sirait, Ritawati (Cattleya Darmaya Fortuna, 2025)
Human Resource Management (HRM) in a company is a strategic approach in managing the workforce so that it can contribute optimally to achieving the company's goals. HRM covers various aspects, such as recruitment, selection, training, development, performance appraisal, compensation, to employment relations and employee welfare. The main objective of HRM is to ensure that the company has a competent, motivated, and productive workforce, and to create a work environment that is conducive to individual and organizational growth. With good management, companies can improve operational efficiency, employee satisfaction, and competitiveness in the market. The recruitment process can lead to subjectivity and unfair decision making. This study aims to implement a Decision Support System (DSS) based on the Simple Additive Weighting (SAW) method to assist the Human Resource Recruitment process needed by a company objectively and systematically. The research methodology uses a quantitative approach with case studies on companies in the recruitment process. Data collection was carried out through surveys, interviews with HR managers, and analysis of historical employee data based on five main criteria: sales performance, creativity, communication skills, work experience, and loyalty. The results showed that the SAW method provides accurate recommendations in determining the best candidates based on their relative proximity to the ideal solution. The analysis also identified that sales performance is the most dominant factor in decision making, with the highest weight. The implementation of a SAW-based Decision Support System can improve the efficiency and accuracy of decision making while reducing subjectivity in the employee recruitment process. The DSS process concluded that this system can be an effective solution in supporting HR decision making based on data-based analysis and objective evaluation.